Introduction to peace and conflict studies - Edmund, Lois., 1951- (Lanham : : Rowman & Littlefield, 2021)
"This book integrates research and theoretical findings from multiple disciplines to present a holistic approach to conflict resolution. It highlights the distinctive and compelling nature of conflict resolution studies by including material on interpersonal relationships, family and group functioning, and national and international relations"--
"Co-published with the Association for Conflict Resolution."
Includes bibliographical references and index.
Keywords: Conflict management; Peace-building.